Effect of maleic acid additive on the preparation and performance of CA/PES blend ultrafiltration membranes. Issue 5 (5th February 2013) - Shobana, K. H.; Krithika, K.; Radha, K. S.; Nagendran, A.; Mohan, D.
ABSTRACT Cellulose acetate (CA) and polyethersulfone (PES) blend ultrafiltration membranes were prepared by phase inversion technique in the presence and absence of additive maleic acid with N, N‐dimethylformamide as solvent. The prepared membranes were characterized in terms of pure water flux, percent water content, and molecular weight cut‐off (MWCO) by solute rejection method. The percentage of rejection of protein such as bovine serum albumin, egg albumin, pepsin, and trypsin were studied. It was found that the pore size of the membrane and the hydrophilicity of CA/PES blend membranes increased with increase in blend composition and additive concentration, which is evident from the increase in water content and the morphological study of the membrane Thus, when the additive concentration in the blend system was enhanced from 0 to 10 wt%, there was an upward trend in the pore radius of the membranes thus enhancing the MWCO of the membrane. The decrease in number of pores also confirms the role of additive in the formation of pores and its interaction with the membrane material during gelation and membrane formation as evidenced by the scanning electron microscope analysis. © 2013 Curtin University of Technology and John Wiley & Sons, Ltd.